RESENHA: FUNARI, P. P. A., CARVALHO, M. M., CARLAN, C., SILVA, E. C. M. (ORGS.) “HISTÓRIA MILITAR DO MUNDO ANTIGO: GUERRAS E REPRESENTAÇÕES”. SÃO PAULO: ANNABLUME, 2012. - Biazotto, Thiago do Amaral (Revista Alétheia, 2014)
Resenha da obra em questão.